2003
DOI: 10.1348/000712603767876253
|View full text |Cite
|
Sign up to set email alerts
|

Student attitudes towards socially acceptable and unacceptable group working practices

Abstract: While there is much support for co-operative learning among learning theorists, not all learners exhibit the same enthusiasm for groupwork. A number of factors such as sex, group size and ability mix, subject domain, task type and organization have been shown to influence the effectiveness of co-operative and collaborative learning. This study established learners' attitudes to various shared working scenarios. In this mixed design, 140 post-graduate teacher trainees were asked to imagine their responses to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 14 publications
8
52
2
Order By: Relevance
“…Even if group work in education has been examined in numerous studies, there is still much to be discovered concerning students' experiences of group work in schools. There are few reports from a student perspective (Cantwell & Andrews, 2002;Hansen, 2006;Peterson & Miller, 2004;Underwood, 2003). To sum up the results, positive experiences resulted from the necessity of all group members participating and showing respect for each other.…”
Section: Students' Experiences Of Group Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Even if group work in education has been examined in numerous studies, there is still much to be discovered concerning students' experiences of group work in schools. There are few reports from a student perspective (Cantwell & Andrews, 2002;Hansen, 2006;Peterson & Miller, 2004;Underwood, 2003). To sum up the results, positive experiences resulted from the necessity of all group members participating and showing respect for each other.…”
Section: Students' Experiences Of Group Workmentioning
confidence: 99%
“…In addition, the students emphasise the importance of understandable goals, tasks, and organisation (Hansen, 2006). According to Underwood (2003) and Peterson and Miller (2004), there is also a problem with students who do not contribute to the group work, so-called free-riders.…”
Section: Students' Experiences Of Group Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies being considered for future implementations of this project class include better guidance about the use of the management group folders, making more explicit the benefits of group sharing and modifications to the assessment requirements so as to reward the transfer of resources from project folders to the management group folder. Research indicates that these factors might exert a positive influence over students' attitudes to group working and resource sharing (Walker, 2001;Underwood, 2003).…”
Section: Improving Resource Sharing and The Role Of Technologymentioning
confidence: 99%
“…This requires that members of the group plan, negotiate and co-ordinate their activities and share information and resources. Research has shown that such collaborative activities can be beneficial to individual learning (Cohen, 1994, Slavin, 1994Quin, Johnson & Johnson, 1995;Johnson, Johnson & Smith, 1998;deCorte, 1998) although it has also been shown that these benefits are dependent on both the quality of the learner interaction and on the attitudes of students to group collaboration (Walker, 2001, Underwood, 2003.…”
Section: Introductionmentioning
confidence: 99%